Restoration of Endothelial Function in Pparα−/− Mice by Tempol. (15th November 2015) - Silswal, Neerupma; Parelkar, Nikhil; Andresen, Jon; Wacker, Michael J.
Abstract : Peroxisome proliferator activated receptor alpha (PPAR α ) is one of the PPAR isoforms belonging to the nuclear hormone receptor superfamily that regulates genes involved in lipid and lipoprotein metabolism. PPAR α is present in the vascular wall and is thought to be involved in protection against vascular disease. To determine if PPAR α contributes to endothelial function, conduit and cerebral resistance arteries were studied in Pparα −/− mice using isometric and isobaric tension myography, respectively. Aortic contractions to PGF2 α and constriction of middle cerebral arteries to phenylephrine were not different between wild type (WT) and Pparα −/− ; however, relaxation/dilation to acetylcholine (ACh) was impaired. There was no difference in relaxation between WT and Pparα −/− aorta to treatment with a nitric oxide (NO) surrogate indicating impairment in endothelial function. Endothelial NO levels as well as NO synthase expression were reduced in Pparα −/− aortas, while superoxide levels were elevated. Two-week feeding with the reactive oxygen species (ROS) scavenger, tempol, normalized ROS levels and rescued the impaired endothelium-mediated relaxation in Pparα −/− mice. These results suggest that Pparα −/− mice have impaired endothelial function caused by decreased NO bioavailability. Therefore, activation of PPAR α receptors may be a therapeutic target for maintaining endothelial function and protection against cardiovascular disease.